(3QSGdI GddaX GdeUQM aj GdYed HGdQHY GdeLfMs - (3eMehO Hf CMeO Hf eMehO GdUGdMj, GdeQTOjs ((3eMeO Hf eMeO Hf EHQGgje GdMQhQi s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3aEfg djS ai GdBdGJ GdadcjI eG jYed Hg ai LejY GdCYeGd ai cd YQV HChVM WQjb ZjQ GdLjH HYOg gPg GdBdg GdJi JSei HGdQHY GdeLfM s
(3BNQgG (B:s
(3aeGbWY GdehQi ef GdeOGQGJ agh GdNGQL ef GdbSeg hdjcf gPG GdcdGe BNQ GdQSGdI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B1022 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B142) s
Keywords: (3Gdadcs